Respuesta :

Answer:

Infinite solutions

Step-by-step explanation:

We can start by rearranging the equation 5 - y = 6x to be in the same order as -12x + 10 = 2y. That gives us -6x + 5 = y; divide -12x + 10 = 2y by 2 to get -6x + 5 = y. We can see the equations are the same line, meaning the system of equations has infinite solutions.

Answer:

infinite

Step-by-step explanation:

first i solved for y from 5-y=6x which is y=5-6x

so i plugged it in in the first equation

-12x+10=2y

-12x+10=2(5-6x)

-12x+10=10-12x

0=0

there are an infinite amount of solutions because each term canceled and the statement is true

ACCESS MORE